Effects of NaOH/urea solution as a solvent and salt crystals as a porogen on the fabrication of porous composite scaffold of bacterial cellulose-chitosan for tissue engineering - Yodsanga, S.; Poeaim, S. (My University, 2024)
A bacterial cellulose-chitosan composite scaffold fabricated through solvent casting-particular leaching method using NaOH/urea solution as a solvent and salt crystals as a porogen revealed a three-dimensional structure with the high porosity investigated by scanning electron microscope. The average porous size of the composite scaffold was between 300 and 500 um. The composite scaffold exhibited high water uptake, indicating to enhance water absorption capacity. The compressive test showed that the composite scaffold had good mechanical strength. Fourier-transform infrared spectroscopy analysis confirmed that bacterial cellulose and chitosan were found to be the main components of the composite scaffold. These results indicated that bacterial cellulose-chitosan composite scaffold could be used for application in tissue engineering.
Keywords: Bacterial cellulose; Chitosan; Composite scaffold; Tissue engineering